Gestão de águas pluviais em pequenas e médias cidades voltada para a adaptação às mudanças climáticas - Michel, Jéssica Andrade (2019)
The adaptation of the cities, in relation to extreme events has been a great challenge. The development of the city culminated in urbanization without planning and with great concentration of population in the urban environment. This process has increased the tensions between urban and natural environment, generating serious consequences for human well-being and the efficiency of infrastructure systems. Heavy rains, accumulating large amounts, results in almost all the floods in the urban environment, situations that, in addition to generating economic losses, endanger population’s lives. In this case, this research seeks suitable alternatives to address these situations, trying to answer which strategies should be implemented in urban governance to better adapt to hydrological events and climate change, especially with regard to floods and recurrent floods in cities of small and medium size in the Região Funcional de Planejamento Nove, in the state of Rio Grande do Sul. The methodology was divided into three phases: first, the characterization of the regions most affected by hydrological events occurred; the identification of structural and non-structural measures, that collaborate with management; and finally, the case study of a regional city with a selection of best practice that best fits to the city . At the end of the first part of the process of hydrological events, 39 municipalities were classified as having high recurrence of floods; Sarandi was selected for the case study. In regional terms, the highest rate of recurrence of floods was found in the cities of the Conselho Regional de Desenvolvimento (Corede) Médio Alto Uruguai. To the good practices, four practices were listed in the total, and also the selection of case studies that collaborated in their understanding and description. The realization of the case study, allowed to reveal the difficulties faced by the city of Sarandi, and it shows the possible causes of the problems. As a part of the case study, a multicriteria analysis was realized, in order bring together the judgment of professionals with knowledge in planning and urban infrastructure, to select the best practice to the city of Sarandi. The Water Sensitive Urban Design (WSUD) was considered the most adequate practice to the city of Sarandi. At the end of the research, the applicability of this study at the regional level was discussed as a tool to study the measures that propose the reduction of recurrent hydrological events in the region.